Determination of Egg Shell Quality with P Control Charts in Poultry - Melis Çelik Güney; Gökhan Tamer Kayaalp (Turkish Journal of Agriculture: Food Science and Technology)
Broken or cracked eggs are important factor in determining the quality of the egg shell. Manufacturers are experience great losses because broken or cracked eggs aren’t evaluated. The manufacturers need control charts throughout the production to determine whether process is under control. In this study, broken and cracked eggs which are taken Cukurova University, Faculty of Agriculture, Department of Animal Science, Poultry Businesses during 52 weeks are determined. P control charts of the data’s are taken in poultry business during 52 weeks is drawn due to determining whether there is under the control. Three methods were used for drawing control charts. In the end of this study, it has been determined to be not under control of the process.